Language education in elementary schools: Meeting the needs of the nation. (13th February 2018) - Rubio, Fernando
Abstract : This article briefly reviews the social, political, and economic context that explains the present status of elementary language education in the United States and addresses the challenges identified by recent reports on the state of language education in the United States. Different curricular models of world language education—exploratory, sequential, and immersion—are discussed in regard to their ability to meet the need, expressed by the profession, to provide universal access to language education and produce graduates who have advanced levels of language proficiency. The article argues that in order to be successful, elementary programs have to be built with support and input from a variety of stakeholders, with careful consideration of the financial and human resources needed and with long‐term articulation plans. A state‐supported immersion program is used to illustrate how the integration of all these factors can lead to successful and scalable programs. Challenges: How can we best prepare learners for success in a world that increasingly values and demands multilingual citizens? To what extent can each of the various existing K–5 instructional models help learners to develop the language proficiency and intercultural skills that they will need to succeed? Video Abstract & Discussion